Optimalisasi Jalur Pedestrian Bagi Pengguna Disabilitas di Jalan Imam Bonjol Semarang - Desetyaningrum, Imbar; Sari, Suzanna Ratih (Jurnal Arsitektur ZONASI, 2021)
Pedestrian ways are one of the important elements of urban design as a connecting and supporting system for urban space’s vitality. Pedestrian ways in a good and accessible condition increases the user’s comfort and helps people with disabilities and special needs to be independent. Pedestrian ways located at Jalan Imam Bonjol Semarang have been renovated by government to increase its function, walkability and estetics aspect. The purpose of this study was to determine and evaluate the optimalisation use of the pedestrian ways at Jalan Imam Bonjol Semarang, especially for persons with special needs and disabilities user. The research uses qualitative approach which describe in descriptive methods, data collection through field observations and literature studies. The results showed that the use of the existing pedestrian ways in Jalan Imam Bonjol is not optimum which is not accessible for disabilities user.